Spatial distribution of a population at risk: an important factor for understanding the recent rise in tick-borne diseases (Lyme borreliosis and tick-borne encephalitis in the Czech Republic) - Zeman, Petr; Benes, Cestmir (Ticks and tick-borne diseases, 2013)
Recent rise in tick-borne diseases in many parts of Europe is a phenomenon in need of an explanation. We analyzed temporal trends in spatial distribution of a population at risk of Lyme borreliosis, tick-borne encephalitis, and as a control, also of a 'non-tick-borne disease' in the Czech Republic in 1997-2010. Analysis revealed that the population's exposure had been increasingly confined to the nearest surroundings of residences or in totally residential locations and that the incidence of the diseases depended in some causal way on how close to residences people exposed themselves to the risk. The rise in Lyme borreliosis and tick-borne encephalitis was solely due to infections acquired at or near patients' homes (<5 km), while the number of cases acquired further away was decreasing. The detected patterns in the data question some of the hypotheses which may be applicable in explaining the rise in disease incidences in the Czech Republic including the effect of climate change. Potentially causal factors are discussed.
Keywords: lymeská nemoc; Spatial Analysis; dospělí; Animals; Spatial analysis; Female; Borrelia burgdorferi; Seasons; Tick-Borne Diseases; dítě; Age Factors; Adult; ženské pohlaví; mladý dospělý; Adolescent; věkové faktory; lidé; nemoci přenášené klíšťaty; roční období; viry klíšťové encefalitidy; Time series analysis; Tick-borne encephalitis; Encephalitis Viruses, Tick-Borne; Risk Factors; Incidence; Sex Factors; Exposure risk; Male; incidence; sexuální faktory; Czech Republic; Lyme borreliosis; Lyme Disease; Young Adult; Encephalitis, Tick-Borne; rizikové faktory; Česká republika; lidé středního věku; Child; zvířata; klíšťová encefalitida; mužské pohlaví; prostorová analýza; Middle Aged; mladiství; Humans